Genome-wide identification and expression analysis of the CHYR gene family in Phaseolus vulgaris under abiotic stress at the seeding stage. Issue 1 (31st December 2023) - Meng, Xianxin; Yin, Zhengong; Yang, Guangdong; Wei, Shuhong; Guo, Yifan; Zhang, Wei; Wang, Qiang
ABSTRACT : Really Interesting New Gene (RING) proteins are referred to as CHY zinc and ring finger protein ( CHYR ) members because they have the CHY domain, a type of protein that responds to abiotic stress. However, there are scant data on CHYR members in Phaseolus vulgaris (common bean). This study identified eight CHYR members ( PvCHYRs ) in the reference genome. A comprehensive analysis was performed to determine function, location, basic information, evolution, motifs, gene structure, cis -acting elements, collinearity, and expression patterns at the seeding stage. The results demonstrated that PvCHYRs might be involved in response to abiotic stressors, whereas some PvCHYRs were screened and can be used as candidate CHYR genes in further research. This study provides a basis for identifying and analyzing PvCHYR members and provides insights for their screening in future research.